1996
DOI: 10.1073/pnas.93.17.8830
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated Ser/Arg-rich proteins: limiting factors in the assembly of 200S large nuclear ribonucleoprotein particles.

Abstract: We have previously shown that specific nuclear pre-mRNA transcripts and their splicing products, as well as the general population of nuclear poly(A)+ RNA, are packaged in large nuclear ribonucleoprotein (InRNP) In view of the proposed role of the SR proteins in premRNA splicing, this family of proteins is expected to be associated with the RNA processing machinery in vivo. PremRNA splicing in vivo apparently occurs on structures more complex than individual spliceosomes. This should not be surprising, becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
53
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 40 publications
(53 reference statements)
5
53
1
Order By: Relevance
“…We previously have shown that when HeLa cell nuclear supernatants were fractionated in sucrose gradients and probed for a specific pre-mRNA (e.g., ␤-actin), a relatively broad but distinct peak of the specific RNA was observed at the 200S region of the gradient (38). All of the nucleoplasmic phosphorylated SR proteins also sedimented as one peak at 200S and were associated exclusively with 200S lnRNP particles (22). Other components of the lnRNP particles, such as the U snRNPs, U2AF, and PTB (19,22) gave a broader distribution across the sucrose gradients and were particularly abundant in smaller complexes that sedimented closer to the top of the gradient.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously have shown that when HeLa cell nuclear supernatants were fractionated in sucrose gradients and probed for a specific pre-mRNA (e.g., ␤-actin), a relatively broad but distinct peak of the specific RNA was observed at the 200S region of the gradient (38). All of the nucleoplasmic phosphorylated SR proteins also sedimented as one peak at 200S and were associated exclusively with 200S lnRNP particles (22). Other components of the lnRNP particles, such as the U snRNPs, U2AF, and PTB (19,22) gave a broader distribution across the sucrose gradients and were particularly abundant in smaller complexes that sedimented closer to the top of the gradient.…”
Section: Resultsmentioning
confidence: 99%
“…These processes have been proposed to be carried out within large nuclear ribonucleoprotein (lnRNP) particles that sediment at 200S in sucrose gradients. The composition of the lnRNP particles (19)(20)(21)(22) is very similar to that of the in vitro-assembled spliceosome (reviewed in refs. 23 and 24).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Nuclear pre-mRNAs together with all pre-mRNA processing components are packaged in supraspliceosomes that represent the native pre-mRNA processing machine (26)(27)(28)(29). These complexes contain all five spliceosomal U small nuclear ribonucleoproteins (snRNPs) (25), as well as splicing factors such as the SR protein family (30), and the ADAR A-to-I RNA editing enzymes (26). Because hUpf1 protein was shown to be involved in NAS (20), we reasoned that it might be associated with supraspliceosomes.…”
Section: Resultsmentioning
confidence: 99%
“…Indirect IPs were performed as described in ref. 30 by using anti-ADAR1 WI9 antibodies (kindly provided by K. Nishikura), antihUpf1 antibodies, or anti-Sm mAb Y12 or a nonrelevant antibody, preimmune anti-rabbit IgG (see SI Materials and Methods). IP yield is expressed as the ratio between the intensity of the immunoprecipitated band [minus background of control lanes (lanes 2 and 3)] and the sum of this intensity and that of the corresponding band in the unbound lane.…”
mentioning
confidence: 99%